2015
DOI: 10.1097/md.0000000000002123
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Circulating MiR-21 in the Diagnosis and Prognosis of Digestive System Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Furthermore, it has been reported that miR-21-5p is upregulated in patients aged >40 years who underwent gastrectomy for potentially curable GC (stage III) and experienced a recurrence ( 43 ). In addition, a meta-analysis study indicated that elevated miR-21 expression levels are correlated with tumor differentiation, lymph node metastasis and TNM stage in digestive tract cancer ( 44 ), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, it has been reported that miR-21-5p is upregulated in patients aged >40 years who underwent gastrectomy for potentially curable GC (stage III) and experienced a recurrence ( 43 ). In addition, a meta-analysis study indicated that elevated miR-21 expression levels are correlated with tumor differentiation, lymph node metastasis and TNM stage in digestive tract cancer ( 44 ), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The observation that miR-21 is highly expressed in the plasma of patients with metastatic neuroendocrine tumors is consistent with its known function and with findings in other malignancies [ 2 ]. Expression of miR-21 has been shown to be associated with proliferation, apoptosis and migration [ 31 ] and involved in invasion, intravasation and metastasis [ 32 , 33 ]. miR-21 is upregulated in glioblastoma [ 34 ], breast cancer [ 35 , 36 ], lung cancer [ 37 ], gastric cancer [ 38 ], colorectal cancer [ 39 ], hepatocellular carcinoma [ 40 ], pancreatic cancer [ 41 ] as well as other tumor types [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-21, which promotes cell proliferation and invasion and is upregulated in many cancers, is one of the most widely investigated miRNAs. 67 , 68 , 69 , 70 In HER2-positive BC, miR-21 was found to be inversely correlated with the expression of PTEN and PDCD4; by triggering an interleukin-6 (IL-6)/STAT3/nuclear factor κB (NF-κB)-mediated signaling loop and activating the PI3K pathway, it is also related to decreased trastuzumab sensitivity. 71 Blocking the action of miR-21 with antisense oligonucleotides (ASOs) re-sensitized resistant cells to the therapeutic effects of trastuzumab.…”
Section: Main Textmentioning
confidence: 99%